Memes, monsters and the digital grotesque - Moreno Almeida, Cristina (British Academy Monographs, 2024)
Investigating the grotesque aesthetics of a postdigital era, Memes, Monsters, and the Digital Grotesque offers a fresh and innovative approach to examining informal politics, monstrous aesthetics, and digital media.